The Youth in Iceland Model and Icelandic Adolescent Mental Health - DeVito, Katerina Maria (2019)
Over the last 20 years, Iceland has made major progress in reducing substance use among its youth. Many credit this impressive reduction to implementation of the Youth in Iceland (YiI) Model. YiI programming aims to prevent substance use by increasing youth social support through strengthening family relationships, peer relationships, community connection, and community engagement. It involves a wide variety of relevant stakeholders, including policymakers, teachers, parents, and youth workers. Specific programming ranges from recreational sports teams to parental neighborhood watches. While studies have indicated that YiI programming has greatly reduced substance use among youth, new data have suggested that mental health problems are rising among Icelandic adolescents. Despite an increase in the prevalence of mental health problems, no studies have explored the impact of YiI programming on Icelandic youth mental health. This mixed-methods project consisted of three studies that evaluated the effect of YiI Model programming on Icelandic adolescent mental health. In the first study, a secondary data analysis of cross-sectional YiI Survey data of all 8th to 10th grade students enrolled in Icelandic public schools was performed to explore the relationship between the YiI Model components and self-reported mental illness symptoms. The annual transnational YiI Survey collects data on demographics, behavior, and other social variables. In the second and third studies, focus groups and interviews were conducted with adolescents and key stakeholders to collect feedback on the YiI Model programming and identify barriers and resources for adolescent mental health. For the secondary data analysis of the YiI Survey data, a multivariate logistic regression model was constructed to relate YiI and mental health scores, including terms for covariates that may confound or bias. To supplement the quantitative component, a content analysis of the transcribed focus groups and interviews was performed to elucidate key themes and ...